2019
DOI: 10.1007/s10734-019-00440-1
|View full text |Cite|
|
Sign up to set email alerts
|

Ratings, rankings, research evaluation: how do Schools of Education behave strategically within stratified UK higher education?

Abstract: While higher education research has paid considerable attention to the impact of both ratings and rankings on universities, less attention has been devoted to how university subunits, such as Schools of Education, are affected by such performance measurements. Anchored in a neo-institutional approach, we analyze the formation of a competitive institutional environment in UK higher education in which ratings and rankings assume a central position in promoting competition among Schools of Education (SoE). We app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Interestingly, over the past two decades, there had been increased autonomy and pressure for accountability (Christensen, 2011). The growing influence of global rankings represents a new global standard for “performative accountability” (Oancea, 2008) to obtain a world-class status (Bak and Kim, 2015; Marques and Powell, 2020). Because HEIs produce “positional goods” that provide access to social prestige and income-earning (Hirsch, 1976), highly reputable HEIs could offer high-value positional goods (Marginson, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, over the past two decades, there had been increased autonomy and pressure for accountability (Christensen, 2011). The growing influence of global rankings represents a new global standard for “performative accountability” (Oancea, 2008) to obtain a world-class status (Bak and Kim, 2015; Marques and Powell, 2020). Because HEIs produce “positional goods” that provide access to social prestige and income-earning (Hirsch, 1976), highly reputable HEIs could offer high-value positional goods (Marginson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found that rankings force “profound transformations” (Hazelkorn, 2011) to make them more proactive about the challenges associated with reflexive transformation (Pollock et al , 2018), particularly in the context of indicators adopted and used by global ranking institutions (Brankovic, 2018). In short, rankings cause universities to implement changes ranging from internal practices to organisational structures (Dahler-Larsen, 2011; Marques and Powell, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Without such conformity to external social pressures, organisations may risk resistance to, or provoke interference in, their activities. It would be very brave (or foolish) of the senior management of a medical school to ignore the current competitive institutional environment of ranking teaching and research, the marketplace of higher education, and neo‐liberal globalisation 12,13 …”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Yet attempts to transform qualities into numeric forms to measure, compare, and inform decision-making reduce the quality of information. This threatens to narrow the recognition and impact of knowledge generated in diverse systems, especially as media companies convert peer review judgements into products to market for profit, such as higher education rankings (Marques et al 2017;Marques and Powell 2019). Further discipline-specific studies are needed to emphasise how research evaluation impacts the structural organisation and cognitive development of research, reinforcing stratification and standardisation.…”
Section: Comparisons Governance Evaluation and Supranational Coordmentioning
confidence: 99%
“…Organizations seeking legitimacy, whether for-profit or not-for-profit, as actors, themselves engage in and manage themselves in competition with generalised others (Hasse and Krücken 2013). Given continuous and world-spanning connectivity, peer review-based ratings of research quality are converted by for-profit media companies into rankings marketed globally for profit, affecting entire higher education systems, organisations, and organisational subunits (Marques and Powell 2019). Continuous research evaluation and policy-driven research programmes distribute competitive grants via peer review at various levels, making not only educational research funding much more competitive.…”
mentioning
confidence: 99%